The development of teacher leadership: a formative interventionist study in a semi-urban secondary school of Khomas region in Namibia - Shilongo, Justina (Rhodes University, Faculty of Education, Department of Education, 2020)
Historically the education system in Namibia was shaped by the policies of the apartheid ideology (Amukugo, 1993). During that time, authority and responsibility were centralised and teachers were not part of the decision making process. By then, most people expected to be told what to do and would not initiate something on their own, a culture inherited that even exists today. In addition, opportunities were not given to teachers to develop as leaders. While Namibians have this history on record, the fact remains that the way in which apartheid laws were put in place, the ideological basis of the policy of apartheid and its impact, was not supportive of the ideas of democracy that Namibia is advocating for today. Despite a number of series of policy guidelines and directives issued to guide the development of a democratic culture in the education sector, less is happening about the leadership of teachers in schools. This stimulated me to conduct an activity theoretical interventionist research, aimed at exploring what opportunities there are for teachers to develop as leaders. This study is a case study, operating from a generative standpoint. The study was conducted in a semi-urban secondary school in Windhoek, Khomas Region, Namibia. The study took a formative intervention approach as it sought to bring about change to practice in the case study school and also to contribute to a body of knowledge in the field of study. This qualitative study employed interviews, observations, document analysis and WhatsApp messaging as data generation tools. Crystallised data revealed multiple realities that demonstrated meaningful and trustworthy data. To analyse data the study employed inductive and abductive analysis to make data meaningful to the reader. Thus, to explore teacher leadership development in a semi-urban secondary school, Change Laboratories Workshops was used as a method to gather and analyse data, as underpinned by 2nd generation CHAT. Grant's (2017) model of teacher leadership was also used to analyse the data and indicate where teacher leadership roles were mostly visible from all four zones. The findings revealed that there were different understandings of the notion of teacher leadership. It was understood as the possession of certain qualities, a managerial role, an involvement in the decision-making process and a form of social responsibility. It was also revealed that teachers led in all four zones (Grant, 2017b), however participants were not active in all the roles. High participation was noticed in zone one, within the classroom; zone two, leading in curricular and extra-curricular activities and zone four, leading beyond the school into the community. This study explored teacher leadership development and at length identified the conditions that constrained and enabled teachers to develop as leaders in a secondary school. The factors that constrained teacher leadership in the case study school were: lack of time, demanding workloads and other commitments, lack of interest in extramural activities and SMT support for initiatives. Fear and unwillingness to take on leadership roles, narrow views on leadership and ingrained traditional leadership structures, limited leadership capacity building initiatives and the absence of clear educational policies on teacher leadership were also identified. The high involvement in zone one, two and four were attributed to some mechanisms the school put in place to promote teacher leadership, such as through various committees set-up, as well as a culture of mutual care and love. During the change laboratory workshops, teachers opted to be trained in leadership-related matters and to revive the CPD committee.
Keywords: Educational leadership -- Namibia; Educational leadership -- Namibia -- Case studies; Education -- Namibia